Adrenergic modulation of melanocortin pathway by hunger signals - Sayar-Atasoy, Nilüfer; Laule, Connor; Aklan, Iltan; Kim, Hyojin; Yavuz, Yavuz; Ates, Tayfun; Coban, Ilknur; Koksalar-Alkan, Fulya; Rysted, Jacob; Davis, Debbie; Singh, Uday; Alp, Muhammed Ikbal; et al. (Nature Communications, 2023)
Norepinephrine (NE) is a well-known appetite regulator, and the nor/adrenergic system is targeted by several anti-obesity drugs. To better understand the circuitry underlying adrenergic appetite control, here we investigated the paraventricular hypothalamic nucleus (PVN), a key brain region that integrates energy signals and receives dense nor/adrenergic input, using a mouse model. We found that PVN NE level increases with signals of energy deficit and decreases with food access. This pattern is recapitulated by the innervating catecholaminergic axon terminals originating from NTSTH-neurons. Optogenetic activation of rostral-NTSTH → PVN projection elicited strong motivation to eat comparable to overnight fasting whereas its inhibition attenuated both fasting-induced & hypoglycemic feeding. We found that NTSTH-axons functionally targeted PVNMC4R-neurons by predominantly inhibiting them, in part, through α1-AR mediated potentiation of GABA release from ARCAgRP presynaptic terminals. Furthermore, glucoprivation suppressed PVNMC4R activity, which was required for hypoglycemic feeding response. These results define an ascending nor/adrenergic circuit, NTSTH → PVNMC4R, that conveys peripheral hunger signals to melanocortin pathway.